2018
DOI: 10.1016/j.quascirev.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mt. Fuji Holocene eruption history reconstructed from proximal lake sediments and high-density radiocarbon dating

Abstract: An 8000-year lacustrine sediment record from Lake Motosu (Fuji Five Lakes) records several eruptions, including potentially unreported events, of the active Mt. Fuji volcano, which receives approximately 47 million annual visitors. A high-fidelity age model is constructed from tephra ages and high-density radiocarbon dating of terrestrial macrofossil and bulk organic matter. Variability in lake reservoir age is constrained by modern lake water radiocarbon measurement and reverse calibration of tephra calendar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…In lacustrine sediments, various methods have been proposed for improving chronologies based on TOC 14 C dating (e.g., Bertrand et al 2012;Hou et al 2012;Obrochta et al 2018). Bowen et al (2019) has recently reported a broad similarity in the 14 C between simultaneously deposited TOC and algal organic matter in sediments of the Great Salt Lake, Utah, and suggested that TOC is little affected by allochthonous organic matter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In lacustrine sediments, various methods have been proposed for improving chronologies based on TOC 14 C dating (e.g., Bertrand et al 2012;Hou et al 2012;Obrochta et al 2018). Bowen et al (2019) has recently reported a broad similarity in the 14 C between simultaneously deposited TOC and algal organic matter in sediments of the Great Salt Lake, Utah, and suggested that TOC is little affected by allochthonous organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…Lake sediments in volcanic regions record valuable information on past eruptions (Koshimizu et al 2007;Van Daele et al 2014;Obrochta et al 2018) and their environmental consequences (Yamamoto et al 2018). Terrestrial plant remains are generally considered ideal 14 C-dating materials in lake sediments because they contain carbon derived directly from atmospheric CO 2 (Bertrand et al 2012) and are rapidly delivered to sediment (Gierga et al 2016); however, terrestrial plant remains are rarely found in volcanic region sediment as volcanisms can severely restrict vegetation cover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in most western lake, Lake Motosu (Figure 1), the watershed vegetation is scarcely covered by Mount Fuji tephras due to the prevailing westerly winds, and therefore the sediments contain abundant plant macrofossils. This allows the construction of a high‐fidelity age model based on high‐density radiocarbon dating of terrestrial macrofossil in Lake Motosu (Obrochta et al., 2018). In contrast, the most eastern lake, Lake Yamanaka (Figure 1), has received a large number of Mount Fuji tephras over the last 15 kyr; however, the occurrence of fossil leaves is significantly limited as compared to Lake Motosu (Yamamoto et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…
Lake sediments in volcanic regions can contain volcanic ash (tephra) deposited by adjacent volcanoes, which provides a unique opportunity to reconstruct continuous volcanic eruption histories (e.g., Kataoka & Nagahashi, 2019;Obrochta et al, 2018;Van Daele et al, 2014) and their environmental consequences (Yamamoto et al, 2018). Radiocarbon ( 14 C) measurement of terrestrial plant remains are generally considered the most reliable method to date lake sediments over the past 50-60,000 years.
…”
mentioning
confidence: 99%